"Raoultibacter massiliensis" gen. nov., sp. nov., a new bacterium isolated from the human gut of a Saudi Bedouin. (November 2016) - Traore, S.I.; Yasir, M.; Azhar, E.I.; Bibi, F.; Bittar, F.; Jiman-Fatani, A.A.; Fournier, P.-E.; Edouard, S.
Abstract: We propose the description of a new bacterial genus and new bacterial species, "Raoultibacter massiliensis, " isolated from a faecal specimen of a 19-year-old healthy Saudi Bedouin.